CLINICAL ANAMNESTIC AND PATHOMORPHOLOGICAL COMPARISON DIAGNOSTIC CRITERIA OF SPINE HERNIATION (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
:      In this study, which was devoted to the study of the pathomorphology of protrusion and hernia injuries belonging to the structural and functional types of degenerative diseases of the spine, the articular surface of the spine was obtained from the symphysis, spinal disc, fibrous ring and nucleus accumbens. Our topographic and morphological study of the above departments of the spine leads to the choice of an effective method of treatment of protrusion and hernia of the spine. In this case, the microscopic structure of the topographic and morphological state of the symphysis and spinal disc was studied. Spinal synchondrosis is densely covered with discs attached to the surfaces of the upper and lower joints. The inner surface of the connecting disk is much thicker, and the fibrous surface, consisting of dense collagen fibers, is surrounded by a layer that is twice as thick as the thick part. Topographic variability of connective tissue in various parts of the connective tissue has been identified, which has been proven in its histological structure. It was found that the fibrous layers in the dense surface layer of the disk consist of collagen fibers in the circular direction, the next inner layer in the radial direction, and the surface side of the vibrating core in the irregular direction.